PEMANFAATAN MEDIA INTERAKTIF DALAM MENINGKATKAN MINAT BACA BUKU SEJARAH PADA ANAK - Mutiara Diaz Fernanda, Alfina; Dewi Pramesta, Aulia Luthfi; Prayitno, Harun Joko; Sari, Dhany Efita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading interest plays an important role in elementary school learning, but students' interest in history books remains low due to lengthy texts, complex language, minimal visuals, and monotonous learning. Therefore, interactive media is used because it can present material in a more visual, concise, and engaging manner in accordance with students' learning characteristics. This study aims to describe the use of interactive media in the form of interactive PowerPoint (interactive PPT) in increasing students' interest in reading history books. This study used a qualitative approach with a case study design involving 22 fifth-grade students of SDN Wonokerto 1, Ngawi Regency. Data were collected through observation, interviews, and documentation during three learning sessions combined with discussions, question and answer sessions, and presentations. The results showed that the use of interactive PPT was able to create more engaging and participatory learning, marked by increased attention, active student participation in asking questions and discussing, and growing interest in history material. The visual and structured presentation of material helped students understand historical concepts more easily and reduced boredom in reading. However, this study has limitations in the limited number of subjects, the context of only one class, and the relatively short duration of the intervention, so that the generalizability of the findings is still limited and requires further research with a wider scope.